Keeping Girls in School : Situation Analysis for Zambia - McConnell, Christin (World Bank, Washington, DC, 2016)
International evidence indicates that keeping girls in school positively impacts their life trajectory and benefits the well-being of the next generation. Zambia has made progress in increasing overall enrollment rates, but additional effort is still needed to ensure that adolescent girls stay in school and complete their education. Starting in the upper grades of primary school, adolescent girls are more likely to drop out of school than their male counterparts with pregnancy, early marriage, and financial constraints frequently cited as the main reasons. There are also noticeable difference in enrollment of Zambian girls across regions and social status. Several on-going initiatives are helping to reduce school fees and create a more supportive school environment, but more information is needed on the current government and non-government programs in place. The quickly growing adolescent population in Zambia will require targeted investments with adequate support mechanisms to keep girls in school and complete a quality education.